indication on the Day of Resurrection in Synodal Slavic Bible - Anatolevich, Rudavin Denis; Viktorovich, Garin Vadim; Igorevich, Pikhota Oleg; Borisovna, Abgaryan Natalia (International Journal of Psychosocial Rehabilitation, 2020)
This article contains an analysis "dark", that is, unintelligible to understand places in the fragment Matt. 28:1 of the text of Slavic Bible in church Slavonic language used at church service. The fragment Matt. 28:1 is important in sense of indication on the real day of the Resurrection of Jesus Christ. The article analyzes determined mistakes on the basis of Greek original text of the New Testament. The texts are being researched by means of “real-philological analysis”, showing and explaining every grammar form in the fragment. As a result of this analysis the article presented Russian translation and proposed corrected translation in church Slavonic language.